Math, asked by shiveshtetakayala, 2 months ago

Prove that sinA/ (1+cot A) - COSA/ (1+tana)
=
sinA-COSA.​

Answers

Answered by mathdude500
9

\large\underline{ \sf{Given \:Question - }}

Prove that,

\rm :\longmapsto\:\dfrac{sinA}{1 + cotA}  - \dfrac{cosA}{1 + tanA}  = sinA \:  -  \: cosA

 \red{\large\underline{\sf{Solution-}}}

Consider, LHS

\rm :\longmapsto\:\dfrac{sinA}{1 + cotA}  - \dfrac{cosA}{1 + tanA}

We know,

\boxed{ \tt{ \: cotx =  \frac{cosx}{sinx}  \: }}

and

\boxed{ \tt{ \: tanx =  \frac{sinx}{cosx} \: }}

So, on substituting these values, we get

\rm \:  =  \:\dfrac{sinA}{1 + \dfrac{cosA}{sinA} }  - \dfrac{cosA}{1 + \dfrac{sinA}{cosA} }

\rm \:  =  \:\dfrac{sinA}{ \dfrac{sinA + cosA}{sinA} }  - \dfrac{cosA}{ \dfrac{cosA + sinA}{cosA} }

\rm \:  =  \:\dfrac{ {cos}^{2}A}{cosA + sinA}  - \dfrac{ {sin}^{2} A}{cosA + sinA}

\rm \:  =  \:\dfrac{ {cos}^{2}A -  {sin}^{2} A}{cosA + sinA}

We know,

\boxed{ \tt{ \:  {x}^{2} -  {y}^{2} = (x + y)(x - y) \: }}

\rm \:  =  \:\dfrac{(sinA + cosA)(sinA - cosA)}{sinA +  cosA}

\rm \:  =  \:sinA - cosA

Hence,

\rm :\longmapsto\:\boxed{ \tt{ \: \dfrac{sinA}{1 + cotA}  - \dfrac{cosA}{1 + tanA}  = sinA-cosA}}

Additional Information:-

Relationship between sides and T ratios

sin θ = Opposite Side/Hypotenuse

cos θ = Adjacent Side/Hypotenuse

tan θ = Opposite Side/Adjacent Side

sec θ = Hypotenuse/Adjacent Side

cosec θ = Hypotenuse/Opposite Side

cot θ = Adjacent Side/Opposite Side

Reciprocal Identities

cosec θ = 1/sin θ

sec θ = 1/cos θ

cot θ = 1/tan θ

sin θ = 1/cosec θ

cos θ = 1/sec θ

tan θ = 1/cot θ

Co-function Identities

sin (90°−x) = cos x

cos (90°−x) = sin x

tan (90°−x) = cot x

cot (90°−x) = tan x

sec (90°−x) = cosec x

cosec (90°−x) = sec x

Fundamental Trigonometric Identities

sin²θ + cos²θ = 1

sec²θ - tan²θ = 1

cosec²θ - cot²θ = 1

Answered by Anonymous
7

Answer:

 \sf\tt\large{\green {\underline {\underline{⚘\;Question :}}}}

 \frac{sin \: A}{1 + cot \: A}  -  \frac{cosA }{1 + tan \: A }  = sin \: A - cos \: A

 \sf\tt\large{\green {\underline {\underline{⚘\;Solution :}}}}

  • Let,

  • Consider, LHS now,

  •  \frac{sin \: A}{1 + cot \: A}  -  \frac{cos \: A}{1 + tan \: A}

Now,

  • Substituting the values we get that,

  •  =  \frac{sin \: A}{1 +  \frac{cos \: A}{sin \: A} }  -  \frac{cos \: A}{1 +  \frac{sin \: A}{cos \: A} }

  •  =  \frac{sin \: A}{ \frac{sin \: A + cos \: A}{sin \: A} }  -  \frac{cos \: A}{ \frac{cos \: A + sin \: A}{cos \: A} }

  • By solving this we get that,

  •    = \frac{ {cos}^{2} A}{cos  \: A + sin \: A}   -  \frac{ {sin}^{2} A}{cos \: A + sin \: A}

  •  =  \frac{ {cos \: }^{2} A -  {sin}^{2} A}{cos \: A + sin \: A}

Now ,

  • Applying the formula that is

 {x}^{2}  -  {y}^{2}  = (x + y)(x - y)

  • From this we get that,

  • Sin A-cosA

Therefore ,

  • LHS=RHS

Hope it helps u mate .

Thank you .

Similar questions